An up-to-date evaluation of cabozantinib for the treatment of renal cell carcinoma. (22nd November 2021) - Marchetti, Andrea; Rosellini, Matteo; Rizzo, Alessandro; Mollica, Veronica; Battelli, Nicola; Massari, Francesco; Santoni, Matteo
ABSTRACT: Introduction : In the evolving treatment scenario of metastatic renal cell carcinoma, cabozantinib is gaining increasing attention, presenting as a cornerstone therapy, both as a monotherapy and in combination with immune-checkpoint inhibitors. Areas covered : In this review, the authors explore the role of cabozantinib in the treatment of metastatic clear cell and non-clear cell renal cell carcinoma, presenting data from the most recent clinical trials and investigating ongoing studies. They, furthermore, evaluate the pharmacokinetic, pharmacodynamic, and immunomodulatory effect of cabozantinib, as well as underlining the tolerability profile and patients' quality of life. Expert opinion : Cabozantinib's administration as a single agent is restricted to intermediate- and poor-risk patients (according to IMDC criteria). The further advent of anti-VEGF-receptor tyrosine kinase inhibitors combined with immune checkpoint inhibitor regimens (such as pembrolizumab + axitinib) has allowed to expand the use of cabozantinib, leading to its combination with nivolumab. In the next few years, more information is required to look for the application of cabozantinib-based combinations as a later-line approach in metastatic RCC patients, beside their use in the first-line setting.